Isang Mapanuring Paghahambing sa Ingles, Filipino, at Sebwanong Mga Salin ng Orihinal na Espanyol na Lyrics ng Pambansang Awit ng Pilipinas - Anastacio, Deborrah S.; Ausa, Gem Carlo B.; Guerrero, Jamie G.; Piguing, Jianne Irissa P.; Romero, Sofia Mae R.; Demeterio III, F.P.A. (Humanities Diliman: A Philippine Journal of Humanities, 2016)
This paper is about the translations made from Palma’s poem “Filipinas” that was used as the official lyrics of the Philippine national anthem. Four texts were examined in this paper: 1) the aforementioned Spanish poem “Filipinas,” 2) Osias and Lane’s English translation entitled “Land of the Morning,” 3) de Leon’s Filipino translation entitled “Lupang Hinirang,” and 4) Vestil’s Cebuano translation entitled “Yutang Tabunon.” This paper aimed to establish how near or far these three translations are from the original poem “Filipinas.” This research is based on the theory of translation proposed by Schleiermacher. Using a Likert scale with a score of 1 to 5, the three translations were compared line by line with the original. The comparative study centered on the meaning and set aside the more complex issues on meter, rhythm, and aesthetics. By getting the average scores of each of the translations, this paper was able to establish that the “Land of the Morning” is moderately near/far from the original, that the “Lupang Hinirang” is near the original, and that the “Yutang Tabunon” is far from the original. Keywords: Jose Palma, “Filipinas,” Camilo Osias, A.L. Lane, “Land of the Morning,” Felipe de Leon, “Lupang Hinirang,” Jess Vestil, “Yutang Tabunon,” Pambansang Awit ng Pilipinas, and Theory of Translation of Friedrich Schleiermacher